Pain chronification and the distinction between acute and chronic pain - Prasad, Ravi (Henry Stewart Talks, 2024)
Psychosocial risk factors associated with chronification of pain, Differences between acute and chronic pain, Coping & other psychological factors, Depression, anxiety, and headache, Pain treatment, Management approach to pain, Interdisciplinary management